A multi-phase mesoscopic simulation model for the diffusion of chloride in concrete under freeze–thaw cycles. (30th December 2020) - Chen, Xuandong; Yu, Aiping; Liu, Guangyan; Chen, Ping; Liang, Qiuqun
Graphical abstract: Abstract: Reinforced concrete (RC) structures in cold regions are subjected to double attacks of chloride erosion and freeze–thaw cycles (FTCs), accelerating the deterioration of concrete performance. Here, a multi-phase mesoscopic numerical model is proposed to systematic study the diffusion mechanism of chloride under the FTCs. Unlike most of existing models, the interface transition zone (ITZ) with random thickness is taken into account in the proposed concrete meso -structure. Moreover, the relationship between FTCs damage and chloride diffusion coefficient of concrete is deduced from the classical Aas-Jakobsen S - N equation. The reliability of the proposed model is further verified by compared with the third-party experiments data. It is evident from the proposed model that FTCs can promote the chloride diffusion. More importantly, this promoting effect is obvious when the number of FTCs is close to the limit number of FTCs. Specially, the mechanism of ITZ promoting the chloride diffusion is revealed by simulating the chloride diffusion trajectories in concrete meso -structure. Interestingly, despite the existence of FTCs in cold regions, chloride is diffused more rapidly in the tropical regions. Our findings reveal previously ignored fundamental aspects of the chloride diffusion mechanism under FTCs, and provide insights for the durability prediction of RC structures.